Molecular flexibility of DNA as a major determinant of RAD51 recruitment - Paoletti, F (2018)
The timely activation of homologous recombination (HR) is essential for the maintenance of genome stability, in which the RAD51 recombinase plays a central role. In vivo, RAD51 polymerises on single-stranded DNA (ssDNA) at double-strand breaks (DSBs) to catalyse HR-dependent DSB repair. Biochemically, human RAD51 polymerises faster on ssDNA compared to double-stranded DNA (dsDNA), raising a key conceptual question: how does it discriminate between them? Throughout this thesis, I tackled this problem by systematically assessing RAD51 binding kinetics on ssDNA and dsDNA differing in length and flexibility using surface plasmon resonance. By fitting detailed polymerisation models informed by the experimental datasets, I suggest that RAD51 is a mechano-sensor that polymerises faster on flexible ssDNA compared to rigid ssDNA or dsDNA. Furthermore, I suggest that the energy released during RAD51 polymerisation is sufficient to overcome any entropic penalty to binding flexible ssDNA. This model presents a new general framework suggesting that the flexibility of DNA, which may increase locally as a result of DNA damage, plays an important role in recruiting repair factors that multimerise at sites of DNA damage.